Contrasting effects of climate change along life stages of a dominant tree species: the importance of soil–climate interactions - Ibáñez, Beatriz; Ibáñez, Inés; Gómez-Aparicio, LORENA; Ruíz-Benito, PALOMA; Garcia, Luis V; Marañón, Teodoro (Diversity and Distributions, 2014)
Aim For tree species, adult survival and seedling and sapling recruitment dynamics are the main processes that determine forest structure and composition. Thus, studying how these two life stages may be affected by climate change in the context of other abiotic and biotic variables is critical to understand future population trends. The aim of this study was to assess the sustainability of cork oak (Quercus suber) forests at the core of its distributional range under future climatic conditions. Location Southern Spain. Methods Using forest inventory data collected at two periods 10 years apart, we performed a comprehensive analysis to evaluate the role of different abiotic and biotic factors on adult survival and recruitment patterns. Results We found that both life stages were influenced by climatic conditions, but in different ways. Adult tree survival was negatively impacted by warmer spring temperatures, while recruitment was positively affected by warmer winter temperatures. Our results also revealed the importance of soil texture as a modulator of winter precipitation effects on adult survival. With higher winter precipitation, adult survival increased in sandy soils and decreased in clayish soils. Therefore, under predicted future climate scenarios of wetter winters and warmer temperatures, the presence of cork oaks is more likely to occur in sandy soils vs. clayish soils. Biotic conditions also affected these life stages. We found a negative effect of heterospecific but not conspecific trees on both adult survival and seedling recruitment. Main conclusions Overall, the sustainability of the studied forests will be highly dependent not only on future climatic trends, but also on their interaction with other key factors – soil properties in particular – that modulate the effects of climate on demographic rates.
Keywords: Bayesian analysis; declining forest; demographic rates; Establishment; forest inventory data; Mediterranean Region